Blogging down a dictatorship - Last Moyo (Communicare)
This article examines the use of blogs to mediate the experiences of citizens during a violent election in Zimbabwe. It focuses specifically on how people disseminated and shared information about their tribulations under a regime that used coercive measures in the face of its crumbling hegemonic edifice. The article frames these practices within theories of alternative media and citizen journalism and argues that digitisation has occasioned new counter-hegemonic spaces and new forms of journalism that are deinstitutionalised and deprofessionalised, and whose radicalism is reflected in both form and content. I argue that this radicalism in part articulates a postmodern philosophy and style as seen in its rejection of the elaborate codes and conventions of mainstream journalism. The Internet is seen as certainly enhancing the people’s right to communicate, but only to a limited extent because of access disparities, on the one hand, and its appropriation by liberal social movements whose configuration is elitist, on the other. I conclude by arguing that the alternative media in Zimbabwe, as reflected by Kubatana’s bloggers, lack the capacity to envision alternative social and political orders outside the neo-liberal framework. This, I contend, is partly because of the political economy of both blogging as a social practice and alternative media as subaltern spaces. Just as the bloggers are embedded to Kubatana’s virtual space to self-publish, Kubatana is likewise embedded to a neo-liberal discourse that is traceable to its funding and financing systems.